2011
DOI: 10.1680/ener.2011.164.4.195
|View full text |Cite
|
Sign up to set email alerts
|

Design for deconstruction and material reuse

Abstract: This paper outlines the importance of taking a whole life-cycle approach when considering the sustainability of buildings, with an emphasis on consideration of the embodied carbon of projects and minimising this when possible. It is suggested that this can be achieved through the specification of reused materials. In order to improve the reused material supply chain in the future it is recommended that new buildings be designed for later deconstruction, thereby maximising the quantity of materials that can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 6 publications
0
48
0
Order By: Relevance
“…Intini and Kuehtz [55] investigated the use of recycled plastic bottles to manufacture thermal insulation in Italy and concluded that recycled polyethylene terephthalate (PET) can reduce environmental impact as much as 46% with respect to GWP. Some researchers also highlight the importance of considering the necessary supply chain to realise this [60].…”
Section: Ms8: Inclusion Of Waste By-product and Used Materials Intomentioning
confidence: 99%
See 1 more Smart Citation
“…Intini and Kuehtz [55] investigated the use of recycled plastic bottles to manufacture thermal insulation in Italy and concluded that recycled polyethylene terephthalate (PET) can reduce environmental impact as much as 46% with respect to GWP. Some researchers also highlight the importance of considering the necessary supply chain to realise this [60].…”
Section: Ms8: Inclusion Of Waste By-product and Used Materials Intomentioning
confidence: 99%
“…However, this strategy is only considered by a handful of studies in the existing literature [e.g. 60,61,78]. In some of the studies, this strategy does not simply consider aiming for a longer service life of the building but is also about designing the building with the necessary flexibility to be durable and adaptable.…”
Section: Ms15: Extending the Building's Lifementioning
confidence: 99%
“…The technical aspects, benefits and costs of reuse of materials and building components, through design for disassembly/deconstruction, have been widely studied in the available literature [92][93][94][95]. If designed properly, many of the elements used in a typical building could be in good enough condition, at the end of the service life of the building, to be reused for similar or other applications [78,91,96].…”
Section: Local Sourcing Of Materials and Componentsmentioning
confidence: 99%
“…To measure the quantity of embodied energy of construction materials, different practical approaches with different study boundaries are adopted. They are commonly known as cradle-to-gate, cradle-tosite, and cradle-to-grave [20]. It should be noticed that these approaches are equally valid to be used to consider the embodied carbon, although the definitions of them below are specifically for embodied energy.…”
Section: Introductionmentioning
confidence: 99%